Nitric oxide dysregulation in the pathogenesis of preeclampsia among Ghanaian women - Adu-Bonsaffoh K; Antwi DA; Obed SA; Gyan B (Dove Medical Press, 2015)
Kwame Adu-Bonsaffoh,1,2 Daniel Ansong Antwi,1 Samuel Amenyi Obed,3 Ben Gyan4 1Department of Physiology, University of Ghana Medical School, Accra, Ghana; 2Department of Obstetrics and Gynecology, Korle Bu Teaching Hospital, Accra, Ghana; 3Department of Obstetrics and Gynecology, University of Ghana Medical School, Accra, Ghana; 4Department of Immunology, Noguchi Memorial Institute for Medical Research, University of Ghana, Accra, Ghana Background: Preeclampsia (PE) is still a disease of theories as the exact cause remains uncertain. Widespread vascular endothelial cell dysfunction is thought to mediate the generalized vasospasm and hypertension characteristic of PE. Altered nitric oxide (NO) production has been associated with the endothelial dysfunction in the pathogenesis of PE but conflicting results have emerged from previous studies. Objectives: To determine maternal serum levels of NO, a biomarker of endothelial function, in nonpregnant, normal pregnant, and preeclamptic women. Materials and methods: This was a cross-sectional case–control study of 277 women comprising 75 nonpregnant, 102 normal pregnant, and 100 preeclamptic women conducted at the Korle Bu Teaching Hospital between April and June 2011. About 5 mL of venous blood was obtained from the participants for the various investigations after meeting the inclusion criteria and signing to a written consent. Serum levels of NO were determined by Griess reaction. The data obtained were analyzed with SPSS version 20. Results: The study showed significantly elevated serum levels of NO in preeclamptic women (82.45±50.31 µM) compared with normal pregnant (33.12±17.81 µM) and nonpregnant (16.92±11.41 µM) women with P<0.001. The alteration in maternal serum NO levels was significantly more profound in early-onset (severe) PE (119.63±45.860 µM) compared to that of late-onset (mild) disease (62.44±40.44 µM) with P<0.001, indicating a more severe vascular endothelial cell dysfunction in the early-onset disease. Conclusion: This study has determined a profound NO upregulation in PE evidenced by significant elevation of NO metabolite levels compared to normal pregnancy. This might be due to deranged endothelial function with dysregulated production of NO to restore the persistent hypertension characteristic of PE. Keywords: preeclampsia, endothelial dysfunction, nitric oxide, Griess reagent